Ketone Ester Intake Did Not Improve Performance, Neither Cognitive Function or Sleep, During an 8-Day Simulated Cycling Race - Louise Engelbrecht; Wout Lauriks; Ruben Robberechts; Myrthe Stalmans; Monique Ramaekers; Elmarie Terblanche; Katrien Koppo; Chiel Poffé (Medicine & Science in Sports & Exercise, 2026)
Purpose: Physiological strain, mental exhaustion, and sleep deprivation are key elements that hinder performance during multi-day endurance activities. Ketone monoester supplementation (KE) may enhance post-exercise recovery, preserve cognitive function, and increase both sleep quantity and quality. Therefore, we simulated an 8-day cycling stage race to assess the effect of KE on physiological strain, mental fatigue, exercise performance, and sleep. Methods: In a double-blind, placebo-controlled, parallel trial, eighteen well-trained cyclists completed the race simulation. (i) Immediately following each stage and (ii) 30 minutes before sleep, the participants received either 25g KE (n = 8) or a taste-matched placebo (n = 10, CON), depending on their group. Body composition, resting metabolic rate, subjective stress-recovery state, mechanical efficiency, 30-minute time trial performance, and m. vastus lateralis biopsies were assessed on the day before and following the race. During the stages, hydration status, subjective markers of fatigue, heart rate, power output, and stage time were collected. Nutritional intake and sleep were measured daily. Results: In both groups, the race induced acute fatigue as evidenced by a drop in peak heart rate (~11 bpm) (P time = 0.002) and time trial performance (~3%) (P time = 0.026). In KE, but not CON, this coincided with an impaired mechanical efficiency at 200W and increased fat oxidation rate by 120% (P interaction = 0.028). Neither KE nor the race had an impact on sleep, dietary intake, or skeletal muscle markers (p > 0.05). Conclusions: The race successfully induced exercise fatigue, but no clear benefit of KE on improved post-exercise recovery, sleep, cognitive function, or endurance performance.